Lean--let's get it right! : how to build a culture of continuous improvement - Rizzardo, David (New York, NY : Routledge, 2020)
"This book addresses the root causes of why a majority of Lean transformations have not met expectations. More importantly, it provides the information needed to turn around the failure mechanisms and transform them into critical success factors. Lean - Let's Get It Right! delves into the psychology of change and motivation and clarifies the roles and responsibility changes which are required for alignment with Lean principles. While the author includes a review of Lean principles, the majority of the book either provides more depth of understanding of the principles or highlights how misalignment can thwart Lean transformation efforts. What this provides is not only clarity, but it establishes a solid reference point or framework to guide the Lean strategy. The reader will begin to see how the principles are not simply a random set of characteristics or features of Lean, but are actually a set of fundamental beliefs on which all else is based. Though repeated throughout the book that an organization must develop the specifics of their own Lean roadmap, this book concludes with guidance on making it happen. This book with its primary focus on people, leadership, and principles, and less so on the details of tools and techniques, can be thought of as providing the few critical missing puzzle pieces to enable an effective Lean transformation"--
List of Action Items. List of Figures. Acknowledgements. About the Author. Introduction. Chapter 1: What is Lean? Chapter 2: Learning from the Past. Chapter 3: The Lean Culture Foundation - The Lean Principles. Chapter 4: Key Support Systems, Tools, and Practices. Chapter 5: Key Roles and Responsibilities. Chapter 6: Resistance, Demotivation, and Motivation. Chapter 7: Making it Happen. Chapter 8: Final Thoughts. Appendix. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Lean manufacturing; Continuous improvement process; Organizational change; Organizational effectiveness; Industrial management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership